Pendampingan Pemberian Imunisasi Dasar Lengkap pada Anak di UPT Puskesmas Medan Tuntungan Kota Medan - Ayu Jani Puspitasari; Muryani Muryani (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
Child immunization programs are very important to improve the health and well-being of children and prevent the spread of deadly infectious diseases. Vaccination is the most important way to prevent disease because it can protect people from serious diseases such as measles, polio, diphtheria, tetanus, and many other diseases that can cause serious complications and even death. This is one of the most effective strategies. In December 2024, community service activities were carried out at the Medan Tuntungan Community Health Center to provide education aimed at increasing parents' understanding and awareness of the importance of complete primary vaccination for their children. The counseling activity was attended by 28 mothers who have babies and toddlers. Participants took part in the activities happily and enthusiastically. The more knowledge mothers gain regarding the importance of complete basic immunization, the better their knowledge regarding complete basic immunization will be and it is hoped that mothers will also have a positive attitude so that there will be a better and increased impact.